Little Smoky Woodland Caribou Calf Survival Enhancement Project - Smith, Kirkby G.; Pittaway, Lois (Rangifer, 2011)
The Little Smoky woodland caribou (Rangifer tarandus) herd is a boreal ecotype located in west central Alberta, Canada. This herd has declined steadily over the past decade and is currently thought to number approximately 80 animals. Factors contributing to the herds' decline appear related to elevated predator-caused mortality rates resulting from industrial caused landscape change. At current rates of decline, the herd is at risk of extirpation. A calf survival enhancement project was initiated in the first half of 2006 as a means of enhancing recruitment while other longer-term approaches were implemented. A total of 10 pregnant females were captured in early March and held in captivity until all calves were at least 3 weeks old. Before release, calves were radiocollared with expandable drop-off collars. Following release, survival of mother and offspring were tracked at intervals until the fall rut. Survival of penned calves was compared to "wild-born" calves at heel of non captive radiocollared females. This approach is compared to other techniques designed to increase recruitment in caribou.